Rancang Bangun Aplikasi Presensi Dengan Metode Local Binary Pattern Histograms dan Geofencing Berbasis Mobile Pada Universitas Dinamika - Moch Khrisna Arsita; Pantjawati Sudarmaningtyas; Erwin Sutomo (Jurnal Sistem Informasi Universitas Dinamika, 2021)
Dinamika university is one of the private campuses in Surabaya that has implemented a attendance management system with attendance recording tool that can be used with biometric validation of faces and fingerprints. The review recording tools available today take a long time for data integration between the tool and the Dinamika university attendance management system, besides the intergration process is not done in real time. The number of tools used is not proportional to the number of employees, causing queues of employees when conducting a review. This final task provides a attendance application development solution that combines two methods namely local binary pattern histograms as biometric validation of face matching and geofencing as validation of restrictions on employee's perspective area, the two methods will be applied to mobile-based applications to overcome queues and record reviews in real time with the Dinamika university attendance management system. The results of the trial of all functional using black box testing showed 100% results. Based on the results of the test, it can be concluded that the local binary pattern histograms and geofencing based on the overall function has been running well.